Assessment of the level of acceptance of the illness and of satisfaction with life in patients with type 2 Diabetes aged 45-60 - Ewelina Bąk; Magdalena Kunc-Małyjurek (Kazimierz Wielki University, 2018)
Background. Type 2 diabetes is a disease which constitutes a serious problem among the middle-aged society. Its progressive nature contributes to the occurrence of numerous limitations in the patients' everyday life. Moreover, the presence of a chronic disease such as type 2 diabetes significantly affects the quality of life. Material and Methods. The studies were performed using the diagnostic poll method. The research tools were: an own survey questionnaire, standardized questionnaires - the Acceptance of Illness Scale (AIS) and the Satisfaction With Life Scale (SWLS). The studies were held from February till December 2017 among 100 inpatients of the cardiology department and the internal medicine department of the Kolejowy Hospital in Wilkowice - Bystra (Independent Public Healthcare Institution). Results. The mean of the acceptance of the illness among patients with type 2 diabetes aged 45-60 was 30.39 which indicates a high level of acceptance. In the SWLS nearly a half of those studied indicated a high sense of satisfaction with life. Conclusions. The patients demonstrated a high level of acceptance of the illness and of satisfaction with life. The level of acceptance determines the sense of satisfaction among patients and affects their quality of life. Keywords: type 2 diabetes, acceptance of the illness, satisfaction with life, chronic disease.